1986
DOI: 10.1136/vr.119.18.444
|View full text |Cite
|
Sign up to set email alerts
|

Acute myopathy in horses at grass in east and south east Scotland

Abstract: A myopathy of horses at grass in east and south east Scotland was recognised in the autumn and winter of 1984 and the spring of 1985. The clinical signs resembled those of paralytic myoglobinuria. Grossly increased creatine kinase activities and the passage of dark brown urine were consistent features. However, the horses were not in training, most of them died and the muscles affected were those of posture and respiration rather than movement. The condition may be unrelated to nutritional myopathy because all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
7

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 0 publications
4
63
0
7
Order By: Relevance
“…In addition, epidemiological surveys had highlighted the seasonality of the disease and its potential link with trees , van Galen et al 2012a). However, previous botanical surveys (Hosie et al 1986, Brandt et al 1997, Puyalto-Moussu et al 2004) had failed to identify any known toxic plant since A. pseudoplatanus, the only tree repeatedly observed on the premises of AM cases (Brandt et al 1997, Puyalto-Moussu et al 2004, van der Kolk et al 2010, was considered safe for horses. In 2012, Valberg and collaborators (Valberg et al 2013) observed that seeds from Acer negundo were always present on all premises inspected where horses had suffered from SPM.…”
Section: Identifying the Cause: Historymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, epidemiological surveys had highlighted the seasonality of the disease and its potential link with trees , van Galen et al 2012a). However, previous botanical surveys (Hosie et al 1986, Brandt et al 1997, Puyalto-Moussu et al 2004) had failed to identify any known toxic plant since A. pseudoplatanus, the only tree repeatedly observed on the premises of AM cases (Brandt et al 1997, Puyalto-Moussu et al 2004, van der Kolk et al 2010, was considered safe for horses. In 2012, Valberg and collaborators (Valberg et al 2013) observed that seeds from Acer negundo were always present on all premises inspected where horses had suffered from SPM.…”
Section: Identifying the Cause: Historymentioning
confidence: 99%
“…Equine atypical myopathy (AM) in Europe has moved from anecdotal reports (Anonymous 1985, Hosie et al 1986, Whitwell et al 1988, Hillam 1991, Robinson 1991, Delguste et al 2002 to large outbreaks (Brandt et al 1997, van Galen et al 2010, van Galen et al 2012a over the years. Nearly 1,600 European cases of AM from about twenty European countries have been reported to the Atypical Myopathy Alert Group (AMAG) via its dedicated website (http//www.myopathie-atypique.be) between autumn 2006 and January 2015.…”
Section: Identifying the Cause: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Por outro lado, os casos de miopatia atípica descritos por Hosie et al (1986) e Votion & Serteyn (2008) não responderam a terapia com vitamina E e Se, o que difere do observado nesse surto onde houve melhora clínica dos animais que não apresentaram decúbito permanente. Já os dois casos que apresentaram decúbito permanente, a terapia não foi eficiente, pois um animal morreu e o outro, apesar de ter sobrevivido, desenvolveu atrofia muscular severa.…”
Section: Discussão E Conclusãounclassified
“…En 1986, une équipe de scientifiques écossais (Hosie et al, 1986) décrivait une série de cas de myopathies aiguës observés chez des chevaux au pré à l'automne 1984 et au printemps 1985 dans l'Est et le Sud Ouest de l'Ecosse. A partir de 1988, plusieurs autres cas sont décrits dans la littérature scientifique : en Angleterre (WHITWELL et al, 1988), en Allemagne (BRANDT et al, 1997) …”
Section: • Introductionunclassified